2021
DOI: 10.1371/journal.pmed.1003405
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fibroblast growth factor 23 and N-terminal pro-B-type natriuretic peptide to identify patients with atrial fibrillation using a high-throughput platform: A validation study

Abstract: Background Large-scale screening for atrial fibrillation (AF) requires reliable methods to identify at-risk populations. Using an experimental semi-quantitative biomarker assay, B-type natriuretic peptide (BNP) and fibroblast growth factor 23 (FGF23) were recently identified as the most suitable biomarkers for detecting AF in combination with simple morphometric parameters (age, sex, and body mass index [BMI]). In this study, we validated the AF model using standardised, high-throughput, high-sensitivity bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Further research is required to determine whether there is any pathophysiology underlying the reported connection 33 . Age, sex, and body mass index, measured on a high-throughput platform, along with raised NT-proBNP and elevated FGF-23, consistently identify individuals with AF 34 .…”
Section: Fibroblast Growth Factor-23mentioning
confidence: 93%
“…Further research is required to determine whether there is any pathophysiology underlying the reported connection 33 . Age, sex, and body mass index, measured on a high-throughput platform, along with raised NT-proBNP and elevated FGF-23, consistently identify individuals with AF 34 .…”
Section: Fibroblast Growth Factor-23mentioning
confidence: 93%
“…Die gleichzeitige Messung von fast 100 kardiovaskulären Biomarkern legt nahe, dass "Fibroblast Growth Faktor 23" (FGF23) bei Vorhofflimmern erhöht ist [10,19]. FGF23 wird im Knochenmark produziert und reguliert den Phosphatstoffwechsel.…”
Section: Kardiovaskuläre Wachstumsfaktorenunclassified
“…The phosphaturic hormone FGF23 is markedly increased in patients with CKD, and dialysis [ 165 , 312 314 ] and has been causally linked to the development of LVH [ 315 ] and LV dysfunction [ 316 ] and arrythmias such as AF [ 317 ]. The calcimimetic agent cinacalcet reduces circulating FGF23 and has been shown to reduce cardiovascular death, sudden cardiac death and heart failure in patients on dialysis [ 318 ].…”
Section: Treatment Of Ckd-associated Cardiomyopathymentioning
confidence: 99%